Stocktaking of tools and approaches to assess system level water productivity in the Aral Sea Basin - Djumaboev, Kakhramon; Akramkhanov, Akmal; Hamidov, Ahmad (2024)
This report was prepared in the framework of Nexus Gains Initiative. This stocktaking activity aimed at reviewing existing tools and approaches to assess system level water productivity and identifying, assessing and prioritizing nexus interventions. The specific objective of this report was to analyze current literature on water–energy–food (WEF) nexus in Central Asia and its relevance to sustainable development goals (SDGs). The report explored the state of knowledge with regard to the use of WEF nexus in Central Asia. Through a systematic qualitative review of the literature, existing scientific knowledge in the area of WEF nexus in Central Asia is mined, and blind spots are detected. By building upon this review, we aim to synthesize existing knowledge and identify existing knowledge gaps and the need for future research on sustainable WEF nexus in Central Asia.